Angka Kejadia Depresi Pada Ibu Hamil Yang Melakukan Antenatal Care (ANC) di Puskesmas Pedesaan - Sitorus, Melati Rosa (Green Publisher Indonesia, 2025)
This study employed a descriptive quantitative cross-sectional design to assess the prevalence and characteristics of depression among pregnant women receiving Antenatal Care (ANC) in a rural region. A total of 51 participants completed the Edinburgh Postnatal Depression Scale (EPDS), and normality testing revealed p = 0.09, confirming that the data distribution was suitable for parametric analysis. The results indicated that 15 respondents (29.4?%) exhibited symptoms of depression during pregnancy. Additional demographic analysis revealed that the majority of these women were between 20 and 35 years of age (80?%), were in their second trimester (53.3?%), and had experienced previous pregnancies (multigravida) (66.7?%). These findings suggest that nearly one-third of pregnant women in this rural setting are at increased risk of depression. Accordingly, the study emphasizes the importance of integrating routine maternal depression screening into ANC services, with a particular focus on high-risk groups, such as multigravida women and those in their second trimester. Establishing such screening as a standard component of care may serve as an effective early intervention strategy to prevent adverse outcomes, including preterm birth, low birth weight, and disruptions in the child’s physical and mental development.